AI-driven digital twin and Industry 4.0 a conceptual framework with applications - Rani, Sita; Bhambri, Pankaj; Kumar, Sachin; Pareek, Piyush Kumar; Elngar, Ahmed A. 1982- (CRC Press, 2024)
"This book presents the role of AI-Driven Digital Twin in the Industry 4.0 ecosystem by focusing on smart manufacturing, sustainable development, and many other applications. It also discusses different case studies and presents an in-depth understanding of the benefits and limitations of using AI and Digital Twin for industrial developments. This reference book is a must-read and is very beneficial to students, researchers, academicians, industry experts, and professionals working in related fields"--
Enthält Literaturangaben und Index
Keywords: Industry 4.0; Artificial intelligence; Digital twins (Computer simulation); Automatic control engineering; Automotive technology & trades; BUSINESS & ECONOMICS / Development / Sustainable Development; COMPUTERS / Artificial Intelligence; COMPUTERS / Database Management / General; COMPUTERS / Social Aspects / General; Databases; Datenbanken; Digital- und Informationstechnologien: soziale und ethische Aspekte; Drahtlostechnologie; Electrical engineering; Engineering: general; Environmental science, engineering & technology; Ethical & social aspects of IT; Fahrzeugbau; Hydraulic engineering; Künstliche Intelligenz; Nachhaltigkeit; Other manufacturing technologies